Effectiveness of Health Education and Short Message Service Reminders Reminders on Iron Supplement Adherence among Pregnant Women - Nare Karapetyan; Lilit Toyonan; Michelle Steenvoorden; Nour Albahri (Journal of Health Innovation and Environmental Education, 2026)
Purpose of the study: This study aimed to evaluate effectiveness structured health professional led education embedded within routine antenatal care in enhancing iron supplement adherence among pregnant women. Methodology: A quasi-experimental pretest–posttest control group design conducted among 120 pregnant women at Masis Maternity Hospital. Participants allocated to intervention group. receiving structured professional-led education with reinforcement or a control group receiving routine care. Primary outcome was iron supplement adherence (≥80% consumption), while secondary outcomes included knowledge score and hemoglobin level changes over 8 weeks. Data analyzed using chi-square tests, independent and paired t-tests, and logistic regression. Main Findings: After 8 weeks, adherence significantly increased to 81.0% in .intervention group compared with 51.7% in control group (p < 0.001). The intervention group was nearly five times more likely to achieve adequate adherence (AOR = 4.83; 95% CI: 2.01–11.61). Knowledge scores improved by +5.27 points in the intervention group versus +1.78 in controls (p < 0.001). Hemoglobin levels increased by 0.86 g/dL in intervention group icompared to 0.32 g/dL control group (p < 0.001). Novelty/Originality of this study: This study advances maternal health practice by reframing health education as a structured, professionally embedded care model rather than a single counseling encounter, demonstrating measurable behavioral and clinical impact within routine antenatal services.